2021
DOI: 10.4081/dr.2021.9262
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic dermatomyositis and prostate cancer: myopathy regression under cancer-directed therapy

Abstract: Prostate cancer is the second most frequent malignancy in men worldwide and the fifth leading cause of death. Dermatomyositis (DM) is a rare idiopathic inflammatory myopathy characterized by musculocutaneous manifestations. However, DM can also present as a paraneoplastic syndrome of an underlying neoplasm. We report a case of a 65-year-old man diagnosed with prostate adenocarcinoma in the setting of severe dysphagia, muscle weakness and a facial erythematous rash. At first, the DM-related symptoms resolved wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…With the effective treatment of tumors, the symptoms and signs of dermatomyositis can be improved, while the symptoms are aggravated when the tumor progresses. [ 14 , 15 ] Before being admitted, the patient had discovered a mediastinal lump that was perhaps a thymoma with no metastases and no evident rash or weakness of the muscles. Multiple metastases of thymoma along with obvious symptoms and signs of dermatomyositis occurred in this admission, which suggested that the progress of dermatomyositis were closely related to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…With the effective treatment of tumors, the symptoms and signs of dermatomyositis can be improved, while the symptoms are aggravated when the tumor progresses. [ 14 , 15 ] Before being admitted, the patient had discovered a mediastinal lump that was perhaps a thymoma with no metastases and no evident rash or weakness of the muscles. Multiple metastases of thymoma along with obvious symptoms and signs of dermatomyositis occurred in this admission, which suggested that the progress of dermatomyositis were closely related to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The following are available online at : Supplementary Material S1: PRISMA 2020 Checklist [ 54 ]; Supplementary Material S2: List of Excluded Studies [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
mentioning
confidence: 99%